Assessing the effect of Alnus roots on hillslope stability in order to use in soil bioengineering - R. Naghdi; S. Maleki; E. Abdi; R. Mousavi; M. Nikooy (Journal of Forest Science, 2013)
The role of plant roots in stabilizing slopes is obvious, but the amount of the effect is varied in different species. The purpose of this study was to evaluate the effect of alder (Alnus subcordata) roots on hillslope stability. The profile trenching method was used to obtain root characteristics and a standard Instron testing machine was used for determining the tensile strength of roots. Direct shear test with undisturbed samples was used for determining the soil strength parameters. Using the results of biotechnical characteristics and the Wu model, the reinforcement effect was calculated. Using the reinforcement values and soil strength parameters and Slip4Ex program, factor of safety with and without vegetation was calculated. The obtained results indicated that the root density and number of roots decreased with increasing depth and the average root area ratio was 0.071% ± 0.01. Tensile strength decreased with increasing diameter of roots following the power function with an average of 16.29 ± 3.10 MPa. The minimum and maximum of reinforcement were 0.55 KPa and 110.76 KPa, respectively. The results of this paper augment the knowledge about biotechnical characteristics of root systems of Alder species and indicate that this species increases the factor of safety about 16.79%.